2013
DOI: 10.1186/2162-3619-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow non-mesenchymal mononuclear cells induce functional differentiation of neuroblastoma cells

Abstract: Less is known about the non-mesenchymal mononuclear cell fraction of human bone marrow on functional adaptation of neuroblastoma cells. Using immunocytochemistry, we showed that bone-marrow mononuclear cell (BMMC)-conditioned medium can induce tyrosine hydroxylase expression in neuroblastoma cells, which is similar to the effect of retinoic acid. Using quantitative RT-PCR, we showed that NGF, CNTF, and BDNF mRNAs were detected in unfractionated BMMC populations from all human donors at different expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Despite these encouraging results, in depth in vitro evidence on the underlying mechanisms of action is largely unknown. The scarce in vitro data on the effect of BMMNCs on regenerative processes showed that BMMNCs exerted protective effects on rat hippocampal brain slices subjected to oxygen and glucose deprivation and that the BMMNC secretome induced neuronal differentiation of SH‐SY5Y neuroblastoma cells . Nonetheless, additional in vitro data supporting the mechanism of action of BMMNC‐based therapy for ischemic stroke are required.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these encouraging results, in depth in vitro evidence on the underlying mechanisms of action is largely unknown. The scarce in vitro data on the effect of BMMNCs on regenerative processes showed that BMMNCs exerted protective effects on rat hippocampal brain slices subjected to oxygen and glucose deprivation and that the BMMNC secretome induced neuronal differentiation of SH‐SY5Y neuroblastoma cells . Nonetheless, additional in vitro data supporting the mechanism of action of BMMNC‐based therapy for ischemic stroke are required.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…94 Despite the promising results with BMMNCs in ischemic stroke from preclinical studies, 61-63, 95, 96 in vitro evidence of the effect of BMMNCs on the above-mentioned mechanisms is scarce. 97,98 Therefore, this review will focus on MSCs and iPSCs as readily available sources of stem cells and compare their efficacy and potential to ameliorate the disease outcome in animal models of ischemic stroke. In addition, novel imaging strategies allowing in vivo tracking of transplanted cells and noninvasive evaluation of brain repair following stroke will be discussed.…”
Section: Stem Cell Sources and Mechanisms Of Action For Cell-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cells confer neuroprotection through various paracrine mechanisms. Depending on the cellular microenvironment, these cells secrete and regulate a plethora of neurotrophic factors that are essential for the nervous system, like nerve growth factor-β (NGF-β, critical for the development and maintenance of the nervous system [52]), ciliary neurotrophic factor (CNTF, promotes neurogenesis [53]), brain-derived neurotrophic factor (BDNF, major role player in neuronal development as well as synaptic plasticity [53]), glial cell-derived neurotrophic factor (GDNF, plays an important role in striatal dopaminergic transport [54]), and angiopoietin 1 (ANG-1, promotes angiogenesis [55]).…”
Section: Paracrine Effectsmentioning
confidence: 99%
“…BMMNCs have been known to confer neuroprotection through various paracrine and somatic mechanisms. These cells secrete and regulate a plethora of neurotrophic factors, like ciliary neurotrophic factor (CNTF) and brain-derived neurotrophic factor (BDNF) 42 , glial cell-derived neurotrophic factor (GDNF) 43 , β-nerve growth factor (β-NGF) 44 , vascular endothelial growth factor (VEGF) 45 , tumor necrosis factor (TNF)-α and interleukins (IL-1α, IL-β, IL-6, IL-10) 46 , granulocyte-colony stimulating factor (G-CSF) 47 , granulocyte macrophage-colony stimulating factor (GM-CSF) 44 , basic fibroblast growth factor (bFGF) 45 , platelet-derived growth factor-BB (PDGF-BB) 44 and angiopoietin 1 (ANG-1) 48 . Sasaki and colleagues show that BMMNCs can differentiate into a myelinating phenotype in vivo and repair demyelinated CNS 49 .…”
Section: Table 1: Changes In Outcome Measures Over a Period Of 18 Monmentioning
confidence: 99%